2010
DOI: 10.1007/s11746-010-1649-z
|View full text |Cite
|
Sign up to set email alerts
|

Production of Low‐trans Fatty Acids Edible Oil by Electrochemical Hydrogenation in a Diaphragm Reactor Under Controlled Conditions

Abstract: Electrochemical hydrogenation is a novel, alternative process for selective hydrogenation of vegetable oils, because of its high extent of hydrogenation and low trans-isomer formation. Electrochemical hydrogenation of soybean oil in a diaphragm reactor with a formate ion concentration of 0.4 mol/l at pH 5.0 under moderate temperature conditions using a current density of 10 mA/cm 2 was investigated to identify the critical conditions affecting the selective hydrogenation reaction and the resulting fatty acid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Several efforts have been devoted to the search of catalysts producing minimal amounts of trans isomers 7–10. Very interesting results on the use of zeolite supported catalysts have recently been reported by the group of Sels in Belgium.…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been devoted to the search of catalysts producing minimal amounts of trans isomers 7–10. Very interesting results on the use of zeolite supported catalysts have recently been reported by the group of Sels in Belgium.…”
Section: Introductionmentioning
confidence: 99%
“…When the loading of the catalyst is higher than 0.23 , especially 0.23-0.25 , oil can gradually be absorbed onto the surface of the catalyst. This phenomenon could be attributed to the sufficient active sites that are made available by the addition of the catalyst and the subsequent reduction of the rate of desorption of hydrogen atoms on the catalyst surface 29 . It can be seen from Table 2 that as the catalyst loading increases, the TFAs in the oil significantly increase.…”
Section: Effect Of Catalyst Loadingmentioning
confidence: 99%
“…In existing electrolytic approaches, two different setups were reported in the literature as pathways capable of transferring the hydrogen donors via various routes. For example, a mediator assisted system, which employs electrolytes such as sodium formate and formic acid, was reported to effectively carry protons to the double bonds of unsaturated fatty acids [9,10]. Yusem and Pintauro [11] reported that soybean oil was hydrogenated by using an electrocatalytic method at 70 °C with a flow-through reactor system operating in batch recycle mode.…”
Section: Introductionmentioning
confidence: 99%